A new species of Brasilycus (Coleoptera: Lycidae) from Peru - Bocakova, Milada; Nascimento, Elynton Alves Do (Zootaxa, 2013)
Brasilycus peruanus sp. nov. is proposed as new to science. Photographs of the habitus, antenna, pronotum, and aedeagus of the single specimen are presented. This new species represents the first record of the genus Brasilycus from Peru and is the fourth species in the genus recorded from South America.